Changes in Oral Health Behaviors Associated With a Nursing Intervention in Primary Care. (May 2019) - Cheng, Jennifer K.; Faniyan, Abiola; Chan Yuen, Jenny; Myers, Tracy; Fleck, Michelle; Burgess, Jane; Williams, Kathryn; Wijeratne, Rashmi; Webster, Romi; Cox, Joanne; Ng, Man Wai
Objective . To describe changes in oral health behaviors following implementation of a nursing intervention targeting children at risk for early childhood caries at an urban 2-site primary care practice. Methods . Nurses used a proprietary Nursing Caries Assessment Tool (N-CAT) to identify behaviors associated with early childhood caries risk, then provided brief focused dental education, fluoride varnish applications, and dental referrals to children without a dental home. We used generalized estimating equation logistic regression models, adjusted for age at visit, to analyze changes in oral health behaviors over time including the following: (1) tooth brushing frequency, (2) use of fluoride toothpaste, and (3) adult help with brushing among children younger than 5 years of age who had at least 2 N-CATs documented during well care visits between April 2013 and June 2015. We also evaluated dietary habits including going to bed with a bottle or sippy cup and sugar-sweetened beverage consumption, as secondary study outcomes during the same time frame. Results. A total of 2097 children with a mean age of 15.8 (SD 7.6) months at the initial visit were included in the analysis; 51% were boys; 28% were black, 36% Hispanic/Latino, 5% white, 2% Asian, and 19% other; 75% were publicly insured. During the study period, significant ( P < .05) improvements were noted across the 3 oral health behaviors studied among children younger than 18 months. Conclusion. Nursing interventions show promise for promoting preventive dental care in primary care settings and deserve further study.